PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 - Nurhasanah, Nurhasanah; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out company size has a significant effect on capital structure, profitability has a significant effect on capital structure, company size has a significant effect on firm value, profitability has a significant effect on firm value, capital structure has a significant effect on firm value, firm size has a significant effect on firm value through capital structure, profitability has a significant effect on firm value through capital structure. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) Based on the results of the study, it is known that firm size has a positive but not significant effect on capital structure, profitability has a positive and significant effect on capital structure, firm size has a positive and significant effect on firm value, profitability has a positive and significant effect on firm value, and capital structure has a positive and significant effect. to firm value, firm size has a positive but not significant effect on firm value through capital structure, profitability has a positive and significant effect on firm value through capital structure.